EXPLORING USER EXPERIENCES IN PROJECT-BASED LEARNING WEBSITE FOR CREATIVE PRODUCT AND ENTREPRENEURSHIP EDUCATION - Kurnia, Septi; Yohana, Corry; Fidhyallah, Nadya Fadillah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This research aims to explore and comprehend user experiences and interaction dynamics in the context of developing a Project-Based Learning (PBL) website for creative product and entrepreneurship education. Qualitative research methods were employed to gain in-depth insights into how students, educators, and other stakeholders experience and interpret the implementation of PBL through the website. The research subjects consisted of 11th-grade students in Online Business and Marketing (BDP) at SMK Negeri 12 Jakarta. The research approach involved data collection through in-depth interviews, participatory observation, and content analysis of interactions within the website. The findings indicate that the developed website received positive validation from media and content experts. Practitioner evaluations from teachers, the vice principal in charge of the curriculum, and student responses demonstrated high acceptance of the website. This research provides profound insights into user experiences and perceptions of PBL-based learning media, contributing significantly to the development of more contextual and project-based learning strategies in the field of education.